Leadership Style dengan Kinerja Perawat Pelaksana di Rumah Sakit Santa Elisabeth Medan Tahun 2024 - Samfriati Sinurat; Ance Siallagan; Cynthia Nainggolan (Universitas Muhammadiyah Manado, 2025)
The role of a leader has a relationship with the performance and success of implementing nurses. Effective leaders can influence in various ways with their leadership style. Leaders provide direction and goals to members with their leadership style. Leadership style is able to influence, be smart in encouraging, motivating, and facilitating their subordinates so that their goals are achieved. According to Lippits and K. White, there are 3 leadership styles, namely authoritarian, democratic, and laissez-faire. This leadership style influences the loyalty of a implementing nurse's performance in implementing nursing care which can be seen in the quality of service provided to patients. Quantitative research, correlational design. Cross-sectional approach measuring the independent variable of the ward head's leadership style and the dependent variable of the implementing nurse's performance and the relationship between the ward head's leadership style and the implementing nurse's performance were carried out once at the same time. The results of the research showed that the majority of democratic leadership styles were 116 respondents (81.1%), the performance of the majority of nurses was in the good category as many as 118 respondents (82.5%), and the relationship between the leadership style of the head of the room and the performance of the implementing nurses in the chi square test with a p value of 0.533 > alpha (0.05), then Ho = There is no relationship between the leadership style of the head of the room and the performance of implementing nurses at Santa Elisabeth Hospital Medan. For implementing nurses who still have the performance of implementing nurses in the sufficient category, they should increase their self-motivation to be more responsible in carrying out their duties as nurses which is part of their work profession.